Docência em Artes Visuais: continuidades e descontinuidades na (re) construção da trajetória profissional. - Biasoli, Carmen Lúcia Abadie (2009)
The present research discusses the problematic of the teaching career in Visual Arts based on the study of professional life cycle, that is, the vital cycle through which the teachers face. Thus, it aimed at investigating the continuities and discontinuities in the (re) construction of teachers professional careers in Visual Arts, defending the idea that significant aspects of both personal and professional life and the teaching moment lived by the teachers interfere both in the construction of this career as well as in a better understanding of the role of the teacher and, consequently, his / her teaching performance. In the field of Visual Arts teaching, this thesis equally reconstructs the history of institutions responsible for the teaching of Arts in our country, focusing more specifically the present situation of the Instituto de Artes e Design (Arts and Design Institute) from the Federal University of Pelotas (UFPel), which was opened back in 1949. The thesis is based in different researches about biographical data, including the ones which concern the different teacher s career phases (centered in the years of professional experience), and the life cycles, indicating the personal dimension as fundamental in the process by which the teachers build their careers and make their work dynamic, making it clear that the professional improvement is associated to the personal improvement, or is also part of it. Besides this, there are contributions from authors who investigate the teaching activity, specially the ones involved with the professionalization, the professional development and the teacher s knowledge, as well as investigators who analyze the school as a culture producer. The methodological approach is biographic-narrative, which enables the teachers to talk about what they know and do, what they did or what they could or should do, that is, it makes possible to make explicit the past dimensions which have an influence on the present situations and its projection into expected action forms. The teachers who participated in the research teach in city public schools in Pelotas in the area of Visual Arts, all having graduated at IAD. The study takes a quanti-qualitative character, as it combines the questionnaire with interviews. The questionnaire involved 40 teachers and enabled to know characteristics and expectations common to the people as a whole. The interviewed was made with 7 teachers, graduated in different phases of the teaching course (according to changes in the educational legislation) and with distinct teaching experience, permitting to understand aspects related to school history; the choice of the career with their determinant factors and expectations; academic history and their influences; remembrances and teaching practical education; teaching career, within its initial years; whether the fact of being a man / woman affected his / her career; the teaching experience, previous and present. For a better understanding of the teaching career, biographical paths were created based on the analysis of the interviews, here so-called biopaths. Another element used to complement the interviews and the analysis of the biographical data were Travelling Images of Art pieces asked by the teachers, chosen by them in order to express the present moment which they have been facing. For the elaboration of phases, the starting point was the principle that the years of career are meaningful to define the beginning of the first phase, called impact (1-6 years), but they were not standards for its end, because the events faced by the teachers, both at schools as well as in their personal lives, were significant for a change of phase. The closeness to the second phase, the personalization one (7-12 years), was justified because the teachers defined a personal teaching style to teach Visual Arts for groups of different levels and schools with different realities, which demands time and maturity, without discharging a faster change provoked by one or another type of event, a critical moment faced by the teacher. The phase of alternation (13-18 years) corresponded to a period in which the teaching experience enabled the teacher to better understand the educational and the teaching system, what he / she can or cannot do, what he / she wants to do or not, the teacher gave him /herself the chance to choose. Finally the fact of being close to the end of the career determined the so-called individualization phase (19-25 years), responsible for the distance between the teacher and the educational problems and the search for personal satisfaction. Therefore, the teaching years are considered meaningful in the professional career, but they are not the ones which define the phases, as the narratives from the teachers prove that the phases constantly mix - or not and one does not place away nor eliminates the possibility of another. Finally, the modifications in the life phases of teachers are caused by the conditions of determined time and places, having occurred due to the opportunities and limitations dealt by each one of them; the crisscrossing of personal histories and the professional careers in these different moments and places configure a singularity in the teaching practice of these teachers. Although all have gone through, in a general way, similar phases in their teaching careers, it was evident that each one have their own and unique life experience and professional career, each with a specific subjective experience, each one of them is unique. To end, it can be said that the understanding of the life cycles, through the phases of the teaching career, crisscrossing personal histories and professional careers in different places and moments of the teaching practice, enables thinking about alternatives and motivating innovation proposals for the initial and continuing teacher s education.